Proposal of public policies regarding the introduction of first aid courses for emergency situations in schools - Sava (Mihalcea) Mirela Camelia; Cucuteanu (Gurei) Rodica Valentina; Pușa (Grosu) Mariana Camelia (Technium Social Sciences Journal, 2020)
Situations such as the fire from the "Colectiv" club, the floods and the last great earthquakes, have shown that the population of Romania is not prepared for such situations and the efforts made so far have not proved their efficiency. In these situations, it is proven that the number of victims could be smaller if those present knew how to rationally manage the situation. The objective of the public policy proposal is to integrate first aid courses in emergency situations in schools.